Heat transport during drying of iron ore pellets - Ljung, Anna-Lena (2006)
Iron ore pellets are LKAB’s most refined product and the company is one of the leading suppliers in the world. There is for competitive reasons a great need for research in order to optimize the production and improve quality. The global goal with this project is to develop a tool with which the drying zone of the straight grate pelletizing plant in Malmberget, Sweden, can be optimized. The aim with this thesis is to make a model of temperature and velocity distribution in the up– draught drying zone, without any regard to moisture content in green balls. The velocity distribution is described by laws of fluid dynamics in porous media. The dominating heat transfer mechanism is convection due to the hot air passing through the pellet charge. The air temperature is calculated from the energy equation and the average temperature of the pellet charge is calculated from a diffusive transport equation. Simulations of velocity and temperature distribution are made with aid of Computational Fluid Dynamics and the software CFX 10.0 is used. Result from simulations show a rapid cooling of air due to the high specific surface area in the porous material. Experiments are performed at the Metallurgical Research Institute AB (MEFOS). The goal is to use experimental results to define unknown material parameters and to validate the simulation model. Two sets of experiments are carried out within the frames of this thesis. The first set has the aim to secure the equipment from possible measurement errors. In the second set of experiments, flow through pellets of different sizes and packing are investigated and compared with available equations. Conclusions are that it is possible to make a heat transfer model in CFX 10.0 which calculates solid and fluid temperature. The experimental equipment at MEFOS is reliable for experiments made on small grains if results are to be implemented in the simulation model. Further investigations are required regarding on how to analyse measurements for particles in the size range of pellets and ...